PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN SHOPEE : (Studi Kasus pada Mahasiswa STKIP PGRI Jombang) - Vicky Mahendra Nur Fahmi; Masruchan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This study aims to determine the effect of promotion and service quality on purchasing decisions on shopee consumers STKIP PGRI Jombang students. This study uses a quantitative approach with a research population of 298 students. The total population is more than 100, so by using simple random sampling, 75 samples are obtained. Data collection is done by using questionnaires and documentation. Each variable was measured using validity and reliability tests. Data analysis used multiple regression analysis with F test, t test, and determination test and used classical assumption test which included normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. From this research, it was found that the promotion results had a significant effect on the purchasing decisions of the students of STKIP PGRI Jombang, as evidenced by a significance value of 0.00 < 0.05. The quality of service has a significant effect on the purchasing decisions of students of STKIP PGRI Jombang, as evidenced by a significance value of 0.00 < 0.05. Promotion and quality of service simultaneously have a significant effect on purchasing decisions in students of STKIP PGRI Jombang, as evidenced by a significance value of 0.00 <0.05, meaning that promotion and service quality together can influence purchasing decisions. This shows that promotions and good service quality will support the purchasing decisions of Pgri Jombanh stkip students as expected.